Relationship between serum vitamin C and serum uric acid in people with different BMIs: results from the NHANES 2017–2018 and Mendelian randomization study - Zhang, Jiajie; Jiang, Hejun; Fu, Guanghui; Wu, Zou; Yao, Yukai; Sun, Jie (Frontiers in Nutrition, 2024)
Objective: To examine the association of overweight/obesity and serum vitamin C (serum VC) with serum uric acid (SUA) and to assess causality using Mendelian randomization (MR).: 4,772 participants from the National Health and Nutrition Examination Survey (NHANES), 2017-2018 were included in this study. Multivariate linear regression, variance inflation factor and quantile regression were used to analyze the relationships between overweight/obesity and serum VC and SUA levels. Secondly, Mendelian randomization (MR) was utilized to mitigate bias and prevent reverse causality in the observational study. Genetic variants associated with obesity (N = 13,848), vitamin C levels (N = 64,979) and serum uric acid levels (N = 343,836) were sourced from the most extensive genome-wide association studies (GWAS). The primary analytical method employed was inverse variance weighted (IVW).Results: Based on the observational study, BMI was positively associated with SUA (β = 0.06, 95% CI: 0.05 to 0.07, P<0.001) and serum VC was negatively associated with SUA (β = -0.14, 95% CI: -0.23 to -0.04, P=0.005). In individuals with overweight/obesity (BMI>=25), the negative effects of serum VC on SUA enhanced with increasing serum VC. High serum VC level (Q4 level, above 1.19 mg/dL) reduced SUA (β= -0.30, 95% CI: -0.47 to -0.14, p<0.001) in individuals with overweight/obesity compared to low serum VC level (Q1 level, below 0.54 mg/dL). IVW-MR analysis revealed a significant association between SUA levels and genetically elevated levels of VC (β= -0.03, 95% CI: -0.06 to -0.00, p=0.029) and obesity (β= 0.06, 95% CI: 0.04 to 0.07, p<0.001).Conclusions: Cross-sectional observational analysis revealed that BMI exhibited a positive correlation with SUA levels and that serum VC was negatively correlated with SUA levels; moreover, moderate serum VC can reduce SUA, especially in individuals with overweight/obesity. There was evidence indicating a causal effect of VC and obesity on SUA. It highlights the importance of VC in the management of SUA levels, particularly in overweight/obese individuals. The findings might be helpful for the management of high SUA levels.